Breakthrough Listen follow-up of the reported transient signal observed at the Arecibo Telescope in the direction of Ross 128. Issue 1 (18th December 2017) - Enriquez, J. Emilio; Siemion, Andrew; Dana, Ryan; Croft, Steve; Méndez, Abel; Xu, Andrew; DeBoer, David; Gajjar, Vishal; Hellbourg, Greg; Isaacson, Howard; Lebofsky, Matt; MacMahon, David H. E.; et al.
Abstract: We undertook observations with the Green Bank Telescope, simultaneously with the 300 m telescope in Arecibo, as a follow-up of a possible flare of radio emission from Ross 128. We report here the non-detections from the GBT observations in C band (4–8 GHz), as well as non-detections in archival data at L band (1.1–1.9 GHz). We suggest that a likely scenario is that the emission comes from one or more satellites passing through the same region of the sky.